Preparation and application of mixed octadecylsilyl- and (3-(C-methylcalix[4]resorcinarene)-hydroxypropoxy)-propylsilyl-appended silica particles as stationary phase for high-performance liquid chromatography - Tan, H.M. (2014)
10.1080/10739149.2011.651674